2017
DOI: 10.3382/ps/pex131
|View full text |Cite
|
Sign up to set email alerts
|

Poultry rearing on perforated plastic floors and the effect on air quality, growth performance, and carcass injuries—Experiment 1: Thermal Comfort

Abstract: The present study investigated the use of perforated plastic floors in the rearing of male and female poultry under thermal comfort conditions. The study was conducted in 2 climate chambers, in one was conventional poultry litter (wood shavings) and in the other was a perforated plastic floor. The experimental design was a completely randomized design with the factors wood shavings and plastic floor. In each chamber, the animals were divided into 16 experimental pens (8 with males and 8 with females) with a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
4
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 25 publications
4
27
4
4
Order By: Relevance
“…This could be explained by the direct dropping of duck feces in NRS, which makes ducks less opportunity to contact with their excreta. Wang et al [44] and Almeida et al [8] reported that FRS had higher microbial contamination and higher concentrations of NH 3 and CO 2 in the air than NRS, hence the better air quality in NRS also helped reduce the burden on duck immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be explained by the direct dropping of duck feces in NRS, which makes ducks less opportunity to contact with their excreta. Wang et al [44] and Almeida et al [8] reported that FRS had higher microbial contamination and higher concentrations of NH 3 and CO 2 in the air than NRS, hence the better air quality in NRS also helped reduce the burden on duck immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Though CRS makes full use of the breeding house space, ducks were vulnerable as individual activities are much constrained [1]. Whereas, FRS is usually to lay a thick pad of 5-10 cm by straw, sawdust or wood shavings on a cement oor [6][7][8], which could absorb excess moisture but has defects in rearing management. Plastic oor net-rearing and wire oor net-rearing are national wide applied NRS.…”
Section: Introductionmentioning
confidence: 99%
“…Almeida ve ark. 8 derin altlık ve plastik ızgara üzerinde yetiştirilen hızlı gelişen genotiplerin kullanıldığı bir çalışmada, derin altlık zeminde yetiştirilen erkek ve dişi hayvanlarda yemden yararlanma oranını sırası ile 1,63 ve 1,72; plastik ızgaralı zeminde erkeklerde 1,64; dişilerde 1,71 bulmuşlar ve yemden yararlanma için zemin sistemleri arasındaki farkın önemsiz olduğunu bildirmişlerdir. Mikulski ve ark.…”
Section: Tartışma Ve Sonuçunclassified
“…Almeida ve ark. 8 odun talaşı kullanılan derin altlık zemin ile plastik ızgaralı zeminin etlik piliçlerin büyüme performansına etkilerini incelediği çalışmada 42 günlük büyütme dönemi sonunda derin altlık sistemde yetiştirilen hayvanlardan erkeklerin canlı ağırlıklarının 3111 gr, dişilerin ise 2708 gr, plastik zemin üzerinde yetiştirilen erkek hayvanların 3167, dişi olanların 2760 gr canlı ağırlığa ulaştıklarını bildirmişler ve gruplar arası farklılıkları önemli bulmuşlardır. Yine aynı çalışmada, derin altlık zeminde yetiştirilen hayvanların yem tüketimleri erkeklerde 5082 gr, dişilerde 4665 gr, yemden yararlanma oranının erkeklerde 1,63; dişilerde 1,72; ölüm olanlarını erkeklerde %5,96; dişilerde %1,08 olarak bulunmuştur.…”
Section: Introductionunclassified
“…However, environmental conditions, human population density, and land availability limit the use of organic or FR farming systems (20). Confined systems such as caged rearing are still used in broiler production (9).…”
Section: Introductionmentioning
confidence: 99%